Search for contact interactions in $μ^+μ^-$ events in $pp$ collisions at $\sqrt{s}=7$ TeV - CMS collaboration (2201 authors) (2013)
Results are reported from a search for the effects of contact interactions using events with a high-mass, oppositely charged muon pair. The events are collected in proton-proton collisions at $\sqrt{s}$ = 7 TeV using the Compact Muon Solenoid detector at the Large Hadron Collider. The data sample corresponds to an integrated luminosity of 5.3 inverse femtobarns. The observed dimuon mass spectrum is consistent with that expected from the standard model. The data are interpreted in the context of a quark- and muon-compositeness model with a left-handed isoscalar current and an energy scale parameter Lambda. The 95% confidence level lower limit on $Λ$ is 9.5 TeV under the assumption of destructive interference between the standard model and contact-interaction amplitudes. For constructive interference, the limit is 13.1 TeV. These limits are comparable to the most stringent ones reported to date.